Clinical outcome of patients treated with endoscopic decompression after failure of detorsion for uncomplicated sigmoid volvulus - Dai Nakamatsu; Tsutomu Nishida; Aya Sugimoto; Kengo Matsumoto; Masashi Yamamoto (DEN Open)
Abstract Background Endoscopic treatment is the first‐line therapy for uncomplicated sigmoid volvulus (SV). However, there are few reports on the clinical course of SV. We investigated the clinical courses of successful and unsuccessful endoscopic detorsions for bowel decompression in patients with uncomplicated SV. Methods Between May 2009 and February 2022, patients with uncomplicated SV who underwent endoscopic detorsion or decompression only if detorsion failed were enrolled. A case analysis (all cases) and a patient analysis (first episode cases) were performed. Outcomes were compared between the detorsion and decompression groups, including length of hospital stay, recurrence rate, and days to readmission due to SV. Results Seventy patients were included in this study. The success rate of endoscopic detorsion of the SV was 28.6%. There were no differences in age, sex, or other characteristics between the two groups. The hospital stay tended to be longer in the decompression group than in the detorsion group. However, there was no difference in the 30‐day, 6‐month, or 12‐month recurrence rate or the number of days to readmission for SV between the two groups in the case and patient analyses. Conclusions This study suggests that endoscopic decompression is a feasible alternative to endoscopic detorsion in patients with uncomplicated SV.